Intellectual Movements, NGOs, and Alternative Media in Medan’s Political Reform Process (1990–2000) - Sumantri, Pulung; Muhajir, Ahmad (Laboratorium Sejarah, Departement Ilmu Sejarah, Fakultas Ilmu Budaya, Universitas Andalas, 2026)
This article examines the existence and role of intellectual movements, non-governmental organizations (NGOs), and alternative media in Medan during the political reform process from 1990 to 2000. The study is situated within the context of the massive waves of riots and protest movements that emerged across Indonesia in 1998, including in Medan, demanding the resignation of President Soeharto. The situation was further intensified by the close relationship between regional political elites and the central government, which gave rise to various political practices and policies perceived as detrimental to society. Such conditions stimulated the emergence of intellectual and civil movements that sought to construct political criticism against the New Order regime. The research employed a qualitative method using a historical approach through the four principal stages of historical research, namely heuristics, source criticism, interpretation, and historiography. The findings demonstrate that intellectual movements in Medan were not only represented through formal student activism but were also developed through NGO networks and alternative media platforms. Alternative media functioned as an important space for disseminating political criticism, constructing public discourse, and articulating issues related to democracy, human rights, and social conditions in Medan. The circulation of alternative media reflected the expansion of public participation in political discourse during the Reform movement. This study shows that the democratization process in Medan was shaped not only by formal political actors but also by interconnected intellectual networks operating through civil society organizations and alternative media.